QUALITY OF EDUCATION IN THE DEVELOPMENTAL ASPECT LEARNING FUNCTIONS - Buhriy, O.V. (Pedagogy of Higher and Secondary Education, 2009)
he article deals with procedure of quality of education evaluation in the copect of developing function in learning.